Pengaruh Simpanan Anggota, Jumlah Anggota, Volume Usaha, dan Modal Sendiri terhadap SHU (Studi pada Koperasi Al-Marwah Masjid Nasional Al-Akbar Surabaya) - Nurdina Nurdina; R.Yudi Sidharta; Rina Fariana; Yovio Annisa Rahmadhoni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study examines the effect of internal cooperative factors on financial performance as proxied by Sisa Hasil Usaha (SHU) at Koperasi Al-Marwah Masjid Nasional Al-Akbar Surabaya. The research is motivated by the decline in SHU during the COVID-19 period, indicating disruptions in cooperative economic activities. This study aims to analyze the influence of members’ savings, number of members, business volume, and own capital on SHU. A quantitative approach with a causal research design was employed using secondary data from Annual Member Meeting (RAT) reports for the period 2017–2024. The data were analyzed using multiple linear regression. The results indicate that members’ savings and the number of members have a significant effect on SHU, while business volume and own capital do not show significant effects. Simultaneously, all independent variables significantly affect SHU; however, the explanatory power of the model remains limited. These findings suggest that cooperative performance is more strongly driven by member participation than by business scale or capital strength. The study implies that cooperatives should prioritize strengthening member participation, trust, and transparency to improve financial performance and ensure sustainability.